Ethyl 4-{[3-(adamantan-1-yl)-4-phenyl-5-sulfanylidene-4,5-dihydro-1H-1,2,4-triazol-1-yl]methyl}piperazine-1-carboxylate - Al-Abdullah, Ebtehal S. (International Union of Crystallography, 2012)
The title molecule, C(26)H(35)N(5)O(2)S, displays a chair-shaped piperazine ring, as well as a planar triazole ring whose phenyl substituent is perpendicular to the mean plane of the five-membered ring [dihedral angle = 90.00 (13)°]. The methylene substituent on the piperazine ring occupies an equatorial site. Weak intermolecular C—H⋯O hydrogen bonding is present in the crystal structure. The crystal studied was a non-merohedral twin, with a 33.9 (3)% minor component.